The The Influence Of Motivation, Discipline And Work Environment On Employee Performance On CV. Gino Guruputra Kab. Tangerang - Adi Polandika; Bambang Mardi Sentosa; Bambang Afriadi (RTTM, 2023)
This study assessed the influence of motivation, discipline, and work environment on employee performance at CV. Validity tests, reliability tests, normalcy tests, descriptive statistical analysis tests, simple linear regression tests, multicollinearity tests, heteroscedasticity tests, multiple regression analysis, determination test, t (partial) test, and f test were used. Results showed that the t test tcount value is greater than ttable, which is equal to tcount motivation of 2.957, Discipline 3.284, Work environment 3.676, and ttable of 1.354. This suggests that motivation, discipline and work environment have a positive and significant effect on employee performance. This study seeks to establish the effect of motivation, discipline, and work environment on the performance of employees at CV. Validity tests, reliability tests, normalcy tests, descriptive statistical analysis tests, simple linear regression tests, multicollinearity tests, heteroscedasticity tests, multiple regression analysis, determination test, t (partial) test, and f test were used. Results showed that motivation, discipline and work environment have a positive and significant effect on employee performance at CV, as demonstrated by a partial test (t test). The F test found a value of 65,947 and a probability value of 0.80, indicating that Motivation, Discipline, and Work Environment all influence Employee Performance at CV simultaneously.